Degree of The Electronic Teaching and its Relation to some Variables among Students in the Primary School (Damascus University Journal of educational and Psychologyical sciences, 2024)
The spread of electronic educational applications increased and their use spread among the categories of students in the basic education stage, so they became able to use them independently, and from here the research problem arises in the need to know the degree of use of electronic educational applications and its relationship to some variables among students of the first stage of education. The primary reason is that students have been affected by it in the recent period, through the use of the descriptive approach and directing a questionnaire to a sample of students in the second, third and fourth grades. The research aims to know the degree of use of electronic educational applications and its relationship to some variables in the schools. The questionnaire in its final form consisted of twenty phrases, and the sample consisted of (230). The originality of this study appears in lack of previous studies, which may help form a starting point for studying the effects of their use on the student, and it falls within the applied field studies. The results showed a large degree in the use of electronic educational applications, and no differences according to any of variables.
Keywords: Degree; Electronic Educational Applications; Basic Eeducation